Assessment of Salivary Levels of the RANKL and RANK in Patients with Healthy Gingiva on Reduced Periodontium Versus Periodontitis: An Analytical Cross-Sectional Study - Shurooq Abdulkareem Muhssin; Hadeel Mazin Akram (Wolters Kluwer Medknow Publications, 2023)
Introduction: We aimed to compare the changes in the two salivary biomarkers, RANKL and RANK, among patients with healthy gingiva on reduced periodontium versus generalized periodontitis stages II and III. Methods: Study subjects were divided into three groups: (1) healthy periodontium (control group) (n = 15), (2) generalized periodontitis stages II and III (n = 30), and (3) healthy gingiva on reduced periodontium (n = 30). Salivary levels of RANKL and RANK were assessed using an enzyme-linked immunosorbent assay. Data analysis was done by the one-way ANOVA and the Tukey post hoc test using R software. Results: There was a statistically significant difference among the three study groups regarding salivary levels of the RANKL (P < 0.001) and RANK (P < 0.001). A Post hoc test showed that the difference between salivary levels of the RANKL (P = 0.50) and RANK (P = 0.86) among periodontitis groups and healthy gingiva in the reduced periodontium group was not statistically significant. Conclusion: High salivary levels of RANKL and RANK in comparison with healthy gingiva are not necessarily associated with the active phase of periodontal disease and progressive bone destruction.